Neuronal conversion of single-chain tissue-type plasminogen activator into its two-chain form: implications in neurodevelopment, learning, and memory - Triniac, Hortense; Lebatard, Simon; Roussel, Valerie; Lechevallier, Charlotte; Lebouvier, Laurent; Vivien, Denis; Roussel, Benoit D. (Cell death & disease, 2025)
Tissue-type plasminogen activator (tPA) is a serine protease expressed in the central nervous system (CNS) that exhibits various effects, from neurodevelopment to learning and memory processes. tPA is secreted in its single-chain form (sc-tPA) and can be cleaved into a two-chain form (tc-tPA), with the two isoforms displaying sometimes opposite effects within the CNS. Using Alexa Fluor-conjugated recombinant tPA and complementary pharmacological approaches, we evaluated the ability of brain cells to process sc- into tc-tPA and the mechanisms involved. Our data revealed that neurons are the main brain cells capable to cleave sc-tPA into tc-tPA. This process occurs in three steps: 1) plasminogen binds to the cell surface of cortical neurons; 2) sc-tPA activates plasminogen into plasmin; 3) the generated plasmin cleaves sc-tPA into tc-tPA. The cleavage of tPA requires its Kringle 2 domain and is independent of plasminogen LBS. This cleavage mechanism represents a new modulation of tPA’s functions within the CNS.